Washington Irving An American Study, 1802-1832 - Hedges, William L. (Johns Hopkins University Press, 2019)
Originally published in 1965. Despite his prolificacy, Washington Irving remained an underexamined figure among literary scholars at the time William L. Hedges published his definitive study of the author in 1965. Most contemporary scholars believed that Irving's central contribution to the American literary tradition was that his work was "polished" and "suave." These scholars maintained that Irving's aristocratic sensibilities defined the stylistic choices of his literary works. To assume this, Hedges contends, is to "both let the man and the work slip beyond one's grasp." Hedges demonstrates that much of Irving's work can be understood in the context of his conflict between federalist and conservative politics. Irving, in other words, found himself incapable of committing to a coherent set of beliefs or attitudes, and this cultural uneasiness manifested itself in his early work. Washington Irving: An American Study, 1802-1832 tries to correct some of the misapprehension about Irving's place in nineteenth-century American literature.